The Role of Intellectual Human Capital, Human Resource Practices and Intention to use of Energy Resources on the Company Performance - Fatihudin, Didin; Sembiring, Murpin Josua; Firmansyah, Muhammad Anang; Holisin, Iis (International Journal of Energy Economics and Policy, 2020)
The study aimed to analyze the relationship between the performance of companies and human capital with the help of moderating role of intention to use of renewable energy through various modes while providing an eminent view of the literature. The approach of quantitative has been used by this study. While reviewing the literature, the permitted issues are covered into three categories which were neglected previously: human capital analysis – relationships of management performance along with the intention to use of renewable energy, measuring and defining of human and intellectual capital, and HRM. Intention to use renewable energy significantly and positively moderates among the relationship between intellectual human capital, and the company’s performance. The results of this study are pertinent to the relationship among various aspects of human resources and performance of companies which were lately experienced in rapid developments. These findings provided the guidelines to the policymakers that they should provide the focus on the formulation of the policies related to the intellectual human capital and effective use of renewable energy that enhance the company performance. Keywords: Human capital, Human resources management, Management Performance, Intentions to use renewable energy JEL Classifications: Q2, J24, O15 DOI: https://doi.org/10.32479/ijeep.10623